2009
DOI: 10.1097/dad.0b013e31819f1997
|View full text |Cite
|
Sign up to set email alerts
|

CD1a and Factor XIIIa Immunohistochemistry in Leprosy: A Possible Role of Dendritic Cells in the Pathogenesis of Mycobacterium leprae Infection

Abstract: Leprosy is a curable chronic granulomatous infectious disease caused by the bacillus Mycobacterium leprae. This organism has a high affinity for skin and peripheral nerve cells. In the evolution of infections, the immune status of patients determines the disease expression. Dendritic cells are antigen-presenting cells that phagocytose particles and microorganisms. In skin, dendritic cells are represented by epidermal Langerhans cells and dermal dendrocytes, which can be identified by expression of CD1a and fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 28 publications
(22 reference statements)
3
12
0
Order By: Relevance
“…They have a role in the cutaneous response to leprosy, which may be a determinant of the course and clinical expression of the disease. [9] Future studies on their contribution, if any, in the carriage and response to the presence of epidermal bacilli might help unravel a few unexplored aspects of leprosy.…”
Section: Discussionmentioning
confidence: 99%
“…They have a role in the cutaneous response to leprosy, which may be a determinant of the course and clinical expression of the disease. [9] Future studies on their contribution, if any, in the carriage and response to the presence of epidermal bacilli might help unravel a few unexplored aspects of leprosy.…”
Section: Discussionmentioning
confidence: 99%
“…33 With respect to LCs in the indeterminate phase of Hansen disease, there are scarce articles about it, dating back over 20 years. 4,[14][15][16][17] This result however needs to be interpreted with caution. Alvarenga et al 19 found no correlation between the clinical forms and the amount of LCs but evaluated only 3 cases of IL, without a control group of normal skin.…”
Section: Discussionmentioning
confidence: 99%
“…This initial interaction between host and bacillus is seldom investigated, with few studies regarding the immune response in this phase. 4 LCs are located mainly at the epidermis and stimulate a wide range of T-cell immune responses. 3 In the skin, major APCs are represented by Langerhans cells (LCs) and some dermal dendrocytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have a role in the cutaneous response to leprosy, which may be a determinant of the course and clinical expression of the disease. [10] Future studies on their contribution, if any, to the carriage of and response to the epidermal bacilli might help unravel a few unexplored aspects of leprosy.…”
Section: Discussionmentioning
confidence: 99%